The relevance of speaking skills with improving digital literacy skills - Muhammadiah, Mas'ud; Pattiasina, Petrus Jacob; Khasanah, Khasanah; Pirdaus, Ali (International research journal of management, IT and social sciences, 2021)
The author believes that learning English, especially speaking skills, is closely related to the mastery of digital literacy skills among students at schools and universities. To prove the assumptions and beliefs of the authors of this study, take a look at some of the data that has been published in various journals, books, and proceedings, as well as other internet data sources. Furthermore, to make it easier for us to answer the questions in this review, we have carried out a series of data analyses and studies by incorporating a coding system and in-depth evaluation and interpretation so that we can derive findings in response to these questions. Study the questions on the basis that, they are valid and reliable. For example, we visited Taylor and Francis Elsevier publications, Google book publications, academic databases, and domestic publication journals. After a series of criticisms of the data and discussion of the findings, we can finally say that there is strong evidence that there is a relevance between successful mastery of speaking skills and digital literacy skills among students. So with these results, we hope that these findings can be input in studies of the success of learning English.